2020
DOI: 10.1097/pep.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

Stander Use in Spinal Muscular Atrophy: Results From a Large Natural History Database

Abstract: Purpose: The purpose of this study was to describe stander use in a natural history cohort of drug therapy-naïve children with spinal muscular atrophy (SMA) who are not walking and identify factors associated with consistent stander use. Methods: Data from 397 children with SMA types 1 and 2 characterized the prevalence and frequency of stander use. Predictors of consistent stander use explored were SMA type, survival motor neuron 2 gene (SMN2) copy num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Most references were eliminated on title and abstract review. Following full-text review of 17 articles only five primary source articles were found to include children diagnosed with SMA-1 [33][34][35][36][37]. See Figure 1 for PRISMA flow chart outlining each phase of the process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most references were eliminated on title and abstract review. Following full-text review of 17 articles only five primary source articles were found to include children diagnosed with SMA-1 [33][34][35][36][37]. See Figure 1 for PRISMA flow chart outlining each phase of the process.…”
Section: Resultsmentioning
confidence: 99%
“…Disabilities 2021, 1, 4 did either did not include or did not explicitly report data from individuals with SMA-1 [38][39][40][41][42][43][44][45][46][47][48][49]. Five articles met inclusion criteria and are included in Table 1; one described power mobility skill development in a case-series of six children including only one child diagnosed as SMA-1 [34]; another described results from an internet-based survey of 32 parents of children with SMA-1 regarding use of speech generating devices and other augmentative communication supports [33]; a third study reported results of a retrospective cohort describing orthotic, positioning and mobility equipment use including 14 children with SMA-1 [35]; a qualitative study explored parents experiences with wheelchair provision and included parents of one child diagnosed as SMA-1 and another described as SMA-1-2 [36]; while a fifth study included data on stander use in 152 children with SMA-1 [37]. Three studies did not include individuals who could be described as 'treated' SMA-1 based on study date [34,35] or explicit statement [37].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations